Las cláusulas exorbitantes en la contratación pública ecuatoriana, en relación con el estado constitucional de derechos y justicia - Germán, Jairo E. (2019)
The present research work was carried out on the Ecuadorian Public Procurement under the perspective of the Constitutional State of Rights and Justice, established in the Constitution of the Republic of 2008, in terms of knowing whether in the mandatory models of the National Public Procurement Service SERCOP It is pertinent to incorporate the so-called exorbitant clauses. For this, the type of documentary research was used with a qualitative approach, applying the doctrinal documentary observation and the duly validated interview guide with structured open questions to experts familiar with the subject matter. The obvious doctrinal confrontation between the classic French schools of Administrative Law and the Spanish and Colombian schools in accordance with the Principle of legality and Constitutional rights and guarantees; In the same way, the interviewees assume a majority position to the Colombian criterion. Concluding that in the mandatory SERCOP model the follow-up of the classic French doctrine is evidenced, although being a State guaranteeing rights, exorbitant clauses would be a complement to the direct application of the National Constitution.